An adaptive methodology for multi-GPU programming in OpenCL. Issue 4 (12th June 2017) - Cavalcanti Bueno, Andre Luis; de La Rocque Rodriguez, Noemi; Dominguez Sotelino, Elisa
Abstract : Purpose: The purpose of this work is to present a methodology that harnesses the computational power of multiple graphics processing units (GPUs) and hides the complexities of tuning GPU parameters from the users. Design/methodology/approach: A methodology for auto-tuning OpenCL configuration parameters has been developed. Findings: This described process helps simplify coding and generates a significant gain in time for each method execution. Originality/value: Most authors develop their GPU applications for specific hardware configurations. In this work, a solution is offered to make the developed code portable to any GPU hardware.